Memorandum of understanding between Universiti Teknologi MARA and Arkitek Azman Zainal / Fakulti Kejuruteraan Awam - Universiti Teknologi MARA, Fakulti Kejuruteraan Awam (Universiti Teknologi MARA (UiTM), 2019)
The purpose of this MoU is to promote collaborative co-operation between Arkitek Azman Zainal with the following objectives: 1. Smart partnership for mutual benefits 2. Promote industry-university knowledge sharing 3. Cooperation and collaboration in research development and commercialization of research 4. Share respective resources and expertise